Inflammatory bowel disease. Issue 5 (21st April 2006) - Beattie, R M; Croft, N M; Fell, J M; Afzal, N A; Heuschkel, R B
Abstract : Twenty five per cent of inflammatory bowel disease presents in childhood. Growth and nutrition are key issues in the management with the aim of treatment being to induce and then maintain disease remission with minimal side effects. Only 25% of Crohn's disease presents with the classic triad of abdominal pain, weight loss, and diarrhoea. Most children with ulcerative colitis have blood in the stool at presentation. Inflammatory markers are usually although not invariably raised at presentation (particularly in Crohn's disease). Full investigation includes upper gastrointestinal endoscopy and ileocolonoscopy. Treatment requires multidisciplinary input as part of a clinical network led by a paediatrician with special expertise in the management of the condition.